ANALISIS UJI KUAT SINYAL TERHADAP JARAK JANGKAU MAKSIMAL SISTEM PENERIMAAN SINYAL INTERNET BERBASIS EDIMAX HP-5101ACK - ., Nindya Naraswari (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Data transfer speed via telephone lines by analogue signals was considered not able to comply with internet users who need the rapid data transfers. This could be covered by Edimax HP-5101 ACK instrument. This research aims to observe signal strenght for maximum distance of internet signal reception system based on Edimax HP-5101 ACK. Determination of QoS parameters were done by measuring access internet speed by speedtest and measuring delay, packet loss and throughput by Axence NetTools Pro 4.0 software. The outcome average of QoS parameters determination of internet access speed on researcher’s home area was 12,11 Mbps for downloading and 1,23 Mbps for uploading. Those values were very good category. The outcome of delay measuring was 51,33 ms (TIPHON: Very Good and ITU-T: Good), jitter was 57,23 ms (TIPHON: Very Good), packet loss was 4,5% (TIPHON: Good and ITU-T: Good) and throughput was 22,932 Kbps (TIPHON: Bad). Besides, the outcome average of QoS parameters determination of internet access speed on Telecommunications Laboratory of Engineering Faculty at Tanjungpura University area was 1,61 Mbps for downloading and 1,94 Mbps for uploading. Those values were good category. The outcome of delay measuring was 106,70 ms (TIPHON: Very Good and ITU-T: Good), jitter was 113,15 ms (TIPHON: Moderate), packet loss was 3,85% (TIPHON: Good and ITU-T: Good) and throughput was 9,257 Kbps (TIPHON: Bad). The decreasing of QoS parameters caused by many internet user there so internet access could not be stable when measuring. Other factors were kind of devices, transmission media and obstacles. Key words: Signal Strength, Parameters of QoS, Access Speed